Pyruvate dehydrogenase B regulates myogenic differentiation via the FoxP1–Arih2 axis. Issue 1 (23rd December 2022) - Jiang, Xuan; Ji, Siyu; Yuan, Fenglai; Li, Tushuai; Cui, Siyuan; Wang, Wei; Ye, Xianlong; Wang, Rong; Chen, Yongquan; Zhu, Shenglong
Abstract: Background: Sarcopenia, the age‐related decline in skeletal muscle mass and function, diminishes life quality in elderly people. Improving the capacity of skeletal muscle differentiation is expected to counteract sarcopenia. However, the mechanisms underlying skeletal muscle differentiation are complex, and effective therapeutic targets are largely unknown. Methods: The human Gene Expression Omnibus database, aged mice and primary skeletal muscle cells were used to assess the expression level of pyruvate dehydrogenase B (PDHB) in human and mouse aged state. d ‐Galactose (d ‐gal)‐induced sarcopenia mouse model and two classic cell models (C2C12 and HSkMC) were used to assess the myogenic effect of PDHB and the underlying mechanisms via immunocytochemistry, western blotting, quantitative real‐time polymerase chain reaction, RNA interference or overexpression, dual‐luciferase reporter assay, RNA sequencing and untargeted metabolomics. Results: We identified that a novel target PDHB promoted myogenic differentiation. PDHB expression decreased in aged mouse muscle relative to the young state (−50% of mRNA level, P < 0.01) and increased during mouse and primary human muscle cell differentiation (+3.97‐fold, P < 0.001 and +3.79‐fold, P < 0.001). Knockdown or overexpression of PDHB modulated the expression of genes related to muscle differentiation, namely, myogenic factor 5 ( Myf5 ) (−46%, P < 0.01 and −27%, P < 0.05; +1.8‐fold, P < 0.01), myogenic differentiation ( MyoD ) (−55%, P < 0.001 and −34%, P < 0.01; +2.27‐fold, P < 0.001), myogenin ( MyoG ) (−60%, P < 0.001 and −70%, P < 0.001; +5.46‐fold, P < 0.001) and myosin heavy chain ( MyHC ) (−70%, P < 0.001 and −69%, P < 0.001; +3.44‐fold, P < 0.001) in both C2C12 cells and HSkMC. Metabolomic and transcriptomic analyses revealed that PDHB knockdown suppressed pyruvate metabolism ( P < 0.001) and up‐regulated ariadne RBR E3 ubiquitin protein ligase 2 (Arih2) (+7.23‐fold, P < 0.001) in cellular catabolic pathways. The role of forkhead box P1 (FoxP1) (+4.18‐fold, P < 0.001)‐mediated Arih2 transcription was the key downstream regulator of PDHB in muscle differentiation. PDHB overexpression improved d ‐gal‐induced muscle atrophy in mice, which was characterized by significant increases in grip strength, muscle mass and mean muscle cross‐sectional area (1.19‐fold to 1.5‐fold, P < 0.01, P < 0.05 and P < 0.001). Conclusions: The comprehensive results show that PDHB plays a sarcoprotective role by suppressing the FoxP1–Arih2 axis and may serve as a therapeutic target in sarcopenia.